Studi Perbandingan Politik Islam Al Mawardi dan Ibnu Taimiyyah Serta Relevansinnya Dengan Politik Demokrasi Modern - Fazari Zul Hasmi Kanggas; Muhammad Azrul Amirullah; Saipul Nasution; Usamah Abdurrahman; Muhammad Akbar Hilman (UIN Mataram, 2026)
The concept of Ahlu al-Halli wa al-‘Aqdi formulated by Al Mawardi in Al-Ahkam al-Sultaniyyah represents an important foundation of classical Islamic political thought concerning leadership selection and governance. This study aims to analyze and critically examine Al Mawardi’s concept of Ahlu al-Halli wa al-‘Aqdi and its relevance to modern democratic politics from the perspective of Ibn Taymiyyah. The research employs a normative juridical and descriptive-analytical approach through the study of classical Islamic political literature and contemporary democratic systems. The findings indicate that Ahlu al-Halli wa al-‘Aqdi functioned as a representative body authorized to appoint and dismiss leaders based on criteria of justice, knowledge, and social influence. However, the mechanism differs significantly from modern democratic institutions such as the People’s Consultative Assembly (MPR), the House of Representatives (DPR), and Regional Representative Councils (DPRD), whose members are directly elected by the people through periodic elections. In Al Mawardi’s framework, leadership succession tended to be elitist and limited to certain authoritative groups. From Ibn Taymiyyah’s perspective, the legitimacy of political authority should prioritize public welfare (maslahah) and justice, allowing flexibility in governance systems according to social and political contexts. The study concludes that although the concept of Ahlu al-Halli wa al-‘Aqdi remains relevant as an ethical foundation for leadership and representation, its implementation requires contextual reinterpretation to align with democratic principles, public participation, accountability, and modern constitutional governance.